Managerial economics for dummies - Graham, Robert J. (John Wiley & Sons, Inc., 2013)
Does the study of managerial economics make your head spin? This hands-on guide helps you make sense of complex business concepts and explains to you in plain English how managerial economics enhances analytical skills, and assists rational decision making.